O 31 de março e a invenção da "Revolução": comemorações e atitudes sociais nos aniversários do golpe de 1964 durante a ditadura militar brasileira - Ana Carolina Zimmermann (2023)
The objective of this dissertation is to investigate the discourses and practices engendered in the aniversaries of the civil-military coup of 1964, during the brasilian military dictatorship, between the years of 1965 e 1984. The analysis is linked in the theoretical discussions of the Cultural History of Politic, mobilizing the concepts of political cultures and imaginary, to reflect about the investments of the autoritarian regime and its supporters in transforming the 31th of march in a relevant commemorative date, with the aim of legitimizing that government, as well the diferentes responses and results that this process generated. The study of civic festivities and political liturgies makes it possible to question the dictatorial efforts in building a positive image of the regime in civil society, as well as to perceive the existing contradictions and conflicts, given that every ritual is subject to differents significations beyond those conferred by its producer. The main historical sources used was news published by major press newspappers (Folha de S. Paulo, Jornal do Brasil, O Estado de S. Paulo e O Globo), literary and didactic publications, historical texts, photographic and audiovisual materials, speeches of political autorities, archives from the political surveillance sistem and legislative documents. Throughout the work, I sought to demonstrate the ways in which the dictatorship appropriated the anniversaries of the 1964 coup, aiming to forge a political imaginary tied to the so-called “Democratic Revolution”. This imaginary has incorporated elements linked to a nationalist-authoritarian political culture, manifesting itself through symbolism (as in the case of civic celebrations) and discursive elements, emphasizing the invention of the "revolutionary ideal" and the framing of history in order to crystallize a version of the coup-laden past aligned with the aims of legitimizing the dictatorship. However, the production of social and collective memories about the event was extremely ambiguous and in constant dispute, with the forms of opposition and resistance that echoed in the festive environment being relevant. For this reason, the celebrations of March 31st remained subject to certain inconsistencies and instabilities, varying greatly due to the historical context experienced and reflecting the existing accommodations within the Brazilian military dictatorship.